73.9k views
5 votes
Square root 3 sin theta = -3 cos theta

1 Answer

3 votes

Answer:

Explanation:

hello : the equation is : √3 sinθ= -3 cosθ means :

sinθ/cosθ = -3/√3

sinθ/cosθ = - √3 because : 3 =√3 ×√3

but : sinθ/cosθ = tan θ

tan θ = - √3 and - √3 = tan( π - π/3) = tan(2 π/3)

you have : tan θ = tan(2 π/3)

note : tanx=tany means : x= y + k π ... k in Z

so : all solutions in R are θ = 2 π/3+k π ... k in Z

User Eduardo Spaki
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.